The Influence of Audit Quality and Internal Audit Control on Earnings Management in Manufacturing Companies in the Consumer Non-Cyclical Sector Listed on the Indonesia Stock Exchange - Aulia Nurannisya Siregar; Heriyati Chrisna; Maf’ul Taufiq (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
The main objective of this study is to analyze the impact of audit quality and internal audit control on earnings management practices. The focus of the observation is on manufacturing companies in the consumer non-cyclicals sector listed on the Indonesia Stock Exchange (IDX). The research method applied is a quantitative approach, using multiple linear regression analysis techniques with SPSS software. Data was collected from eight companies that met the purposive sampling criteria: The research findings indicate the following: Audit Quality (X1): Based on the t-test, the significance value obtained is 0.162 (> 0.05). This indicates that audit quality does not have a significant effect on earnings management. Internal Audit Control (X2): The t-test resulted in a significance value of 0.936 (> 0.05). This means that internal audit control does not have a significant effect on earnings management. Simultaneous Test (F-test): The significance level is 0.337 (> 0.05). Thus, collectively, audit quality and internal audit control do not have a significant influence on earnings management.